Two new species of Sabatieria de Rouville, 1903 (Nematoda: Araeolaimida: Comesomatidae) from the Southern Ocean - Fu, Sujing; Zhang, Shuyi; Leduc, Daniel; Mou, Jianfeng; Lin, Heshan (Zootaxa, 2023)
Two new free-living marine nematode species of the genus Sabatieria de Rouville, 1903 are described from the Southern Ocean using morphological and molecular data. Sabatieria brevicaudata sp. nov. is characterized by body length 1476–1740 μm, short cephalic setae, 13–24% corresponding body diameter long, lateral differentiation of body cuticle with only slightly coarser punctations, spiral amphidial fovea with 3 turns, spicules arcuated and 1.3–1.6 cloacal body diameter long, slightly arcuated gubernacular apophyses, and twelve precloacal supplements, in the form of small pores. Sabatieria multipora sp. nov. is characterized by body length 2139–2324 μm, short cephalic setae (4–7 μm long, 30–40% corresponding body diameter long), cuticle with lateral differentiation of distinctly coarser punctations extending from anterior edge of amphidial fovea to anterior of intestine and in the tail region, spiral amphidial fovea with 3 turns, males with spicules 1.9–2.0 cloacal body diameter long, seventeen fine tubular precloacal supplements with distance between adjacent supplements increasing towards anterior, and with curved gubernacular apophyses. We obtained 18S rDNA and 28S rDNA sequences from the two new species, which are both closely related to other species of Sabatieria. Our analyses also show that several genera of Comesomatidae Filipjev, 1918 do not form monophyletic clades.